2015
DOI: 10.1002/alr.21574
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term outcomes in medial flap inferior turbinoplasty are superior to submucosal electrocautery and submucosal powered turbinate reduction

Abstract: The medial flap turbinoplasty provided consistent, robust results. Long-term relief of obstructive symptoms without additional risk of complication was observed in the turbinoplasty group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 11 publications
(10 reference statements)
3
21
0
Order By: Relevance
“…Cingi et al, Chieh-Feng et al, Albu et al, all of them reported that gradual decrement in postoperative pain and no patient had pain at 1 and 3 months following the surgery and this was comparable to our study. 20,30,32 No synechiae was reported during the follow up period after surgery, this might be due to placement of surgicel and silastic sheets (no raw area), and this agreed with Cingi et al, Hesham et al 10,20 No epiphora was observed from the 1 st week to the 3 rd month following the surgery, this might correlated with Barham et al, Hesham et al 10,33 …”
Section: Post-operative Complicationssupporting
confidence: 59%
“…Cingi et al, Chieh-Feng et al, Albu et al, all of them reported that gradual decrement in postoperative pain and no patient had pain at 1 and 3 months following the surgery and this was comparable to our study. 20,30,32 No synechiae was reported during the follow up period after surgery, this might be due to placement of surgicel and silastic sheets (no raw area), and this agreed with Cingi et al, Hesham et al 10,20 No epiphora was observed from the 1 st week to the 3 rd month following the surgery, this might correlated with Barham et al, Hesham et al 10,33 …”
Section: Post-operative Complicationssupporting
confidence: 59%
“…Existing studies of microdebrider‐assisted submucosal resection report increased rhinomanometric nasal airflow, decreased nasal airway resistance, and greater improvement in patient‐determined nasal obstruction compared to preoperative or healthy controls . Other studies suggest longer efficacy for medial flap turbinoplasty beginning between 12 and 24 months, with lower reported revision rates (12%) compared to electrocautery (54%) or powered submucosal resection (i.e., microdebrider; 40%) during 60‐month follow‐up (n = 100) . These studies are limited by the lack of standardized outcomes, with measures based on rhinomanometry and acoustic rhinometry of unclear clinical significance given the lack of established correlation with PROMs .…”
Section: Discussionmentioning
confidence: 99%
“…To perform fine surgical maneuvers underwater, surgeons must perform fine manipulations in the narrow nasal space, which resembles a small pocket, while avoiding tears in the IT mucosa. Second, SIT may lead to atrophic rhinitis; however, this complication has not been reported in two articles evaluating the long-term results of SIT (6, 7). Similarly, we have not experienced atrophic rhinitis in our cases.…”
Section: Discussionmentioning
confidence: 99%